Retracted: Intrusion detection in cloud environment using hybrid genetic algorithm and back propagation neural network. (9th November 2020) - S, Manimurugan; P, Manimegalai; Valsalan, Prajoona; J, Krishnadas; C, Narmatha
Summary: S M, P M, Valsalan P, J K, C N. Intrusion detection in cloud environment using hybrid genetic algorithm and back propagation neural network, International Journal of Communication Systems 2020, (https://doi.org/10.1002/dac.4667 ). The above article published online on 09 November 2020 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the Editor and John Wiley and Sons Ltd. Following publication, it has come to our attention that the people named as the Guest Editors of the Special Issue were being impersonated by a fraudulent entity and the articles were not reviewed in line with the journal's peer review standards. The Editor has determined that the articles do not meet the required scholarly standards of the journal, and therefore has taken the decision to retract the article. We did not find any evidence of misconduct by the authors. The authors have been informed of the decision to retract.